Why People Leave: Factors Affecting Russian Employees’ Intentions to Change the Organization - ЭфендиевАзер Гамид оглы; БалабановаЕвгения Сергеевна; ЯрыгинаЕлена Олеговна (Journal of Economic Sociology, 2012)
Each organization has to deal with employee turnover issues implying a process of employees’ interfirm mobility and worker quits. The paper focuses on voluntary turnover when employees leave organizations at their own will. The paper aims at examining factors affecting Russian employees’ intentions to leave or to stay in organizations. Based on a sample of 2380 respondents from 80 firms in eight Russian regions, the authors found out that wage satisfaction is dominant but not exclusive factor of Russian employees’ decisions with regard to their interfirm mobility. Work content, autonomy at the work place, and career prospects are also highly significant predictors. In contrast to previous research conducted in foreign companies, the presented research findings do not reveal the significance of social relations and psychological atmosphere as important factors influencing employees’ intentions to leave or to stay in organizations. This suggests stronger “mercenary–individualistic” orientations of Russian workers in comparison with Western labour markets. The authors concluded that an organization’s attempts to retain the more desirable employees should be based on “rules of games” established within the organizational field rather than specific practices of human resource management.